2016
DOI: 10.1177/2167479516660037
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Coach Confirmation

Abstract: The lack of appropriate measurement to assess athlete-coach interaction and athletes’ psychological states has historically plagued sport studies research (i.e., an encompassing term for sport psychology, management, sociology, and communication) and may partially explain the lack of empirical research regarding athlete-coach interaction within the emerging field of sport communication. Without valid and reliable tools to assess athlete-coach interactions, understanding the antecedents and outcomes of these re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Similar to the relationship between teacher and student (Ginott, 1972), coaches need to consistently communicate both acceptance and acknowledgment to their ath letes, while being cautious of athletes' feelings and any potential struggles that may be perceived (i.e., communicate in a nonjudgmental and cooperative manner). When coaches integrate confirming behav iors (e.g., endorsement, recognition, acknowl edgment) into their daily training routines and encourage an environment founded on achievable expectations, goal instrumentality, accountability, and systematic and fair review of performance, athletes will not only achieve positive performance based results but also experience positive affect, enhanced social interactions, and increased moti vation to participate (Cranmer & Brann, 2015;Cranmer, Brann, & Anzur, 2016;Cranmer, Brann, & Weber, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the relationship between teacher and student (Ginott, 1972), coaches need to consistently communicate both acceptance and acknowledgment to their ath letes, while being cautious of athletes' feelings and any potential struggles that may be perceived (i.e., communicate in a nonjudgmental and cooperative manner). When coaches integrate confirming behav iors (e.g., endorsement, recognition, acknowl edgment) into their daily training routines and encourage an environment founded on achievable expectations, goal instrumentality, accountability, and systematic and fair review of performance, athletes will not only achieve positive performance based results but also experience positive affect, enhanced social interactions, and increased moti vation to participate (Cranmer & Brann, 2015;Cranmer, Brann, & Anzur, 2016;Cranmer, Brann, & Weber, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In this research, the Coach Confirmation Instrument was used (Cranmer, Brann, and Weber 2017). Challenge and acceptance together accounted for 68.82% of the variation in the first trial.…”
Section: Instrumentmentioning
confidence: 99%
“…After studying over 500 soccer players aged from 13 to 20 years old, Høigaard et al (2017) found that positive/instructive feedback with a sense of humor could develop team identity among young players. More recently, Cranmer, Brann, and Weber (2018) found that athletes exhibited more satisfaction and higher motivation when their coaches challenge them through constructive criticism and a focus on development. In summary, athletes who perceived receiving more positive and informational feedback, less criticism or punishment, tended to report more positive achievement-related outcomes, including higher levels of perceived competence.…”
Section: Positive Feedbackmentioning
confidence: 99%